Perceived Supervisor Support Dan Job Demand Terhadap Burnout Pada Karyawan PT. XYZ - Almansyah Rundu Wonua; Andry Stepahnie Titing; Febby Annisa Djamaris (Transformasi: Journal of Economics and Business Management, 2023)
This study aims to determine: (1) The effect of perceived supervisor support on employee burnout at PT XYZ in Kolaka Regency. (2) The effect of job demand on employee burnout at PT XYZ in Kolaka Regency. This research uses a quantitative method approach. Data collection in this study used observation, literature study, questionnaires. The population of this study were employees of PT XYZ in Kolaka Regency. Meanwhile, the sample in this study amounted to 55 people. Testing research instruments using validity tests and reliability tests with SPSS 25.0. The data analysis technique used in this study is the model instrument test (outher model) and structural model testing (Inner model) with Smart PLS 3.0. Based on the results of the study, it is known that there is a negative and significant influence between the variable perceived supervisor support on burnout as indicated by the T-statistic value of (1.977) with a P-value of (0.024). while the job demand variable has a positive and significant effect on burnout as indicated by the T-statistic value of (6.131) with a P-value of (0.000).